Analysis of PGT‐M and PGT‐SR outcomes at a Canadian fertility clinic. (26th June 2019) - Butler, Rachel; Nakhuda, Gary; Guimond, Colleen; Jing, Chen; Lee, Nora; Hitkari, Jason; Tallon, Niamh; Taylor, Beth; Yuzpe, Albert
Abstract: Objective: Outcomes from in vitro fertilization (IVF)/intrauterine insemination (ICSI) cycles for patients who underwent preimplantation genetic testing for monogenic/single gene (PGT‐M) and structural chromosome rearrangements (PGT‐SR) patients were reviewed. Patients pursuing PGT‐M and PGT‐SR often do not have pre‐existing fertility issues and therefore may have uncertain expectations of successful outcomes. Before pursuing PGT‐M and PGT‐SR, patients require evidence‐based counseling regarding the probability of having a healthy child. Method: Retrospective review from a single private IVF clinic of 73 PGT patients, from whom a total of 437 blastocysts were biopsied and screened. Embryo results and pregnancy outcomes were analyzed. Results: Of the 45 PGT‐M patients, 64.4% had at least one euploid unaffected embryo. The cumulative pregnancy rate for patients who had embryo transfers in this group was 89.7%, with an ongoing pregnancy or delivery rate of 48.9%. For the 28 PGT‐SR patients, 60.7% had at least one euploid unaffected embryo. The cumulative pregnancy rate for patients who had embryo transfers in this group was 87.5%, with an ongoing pregnancy or delivery rate of 42.9%. Conclusion: This information can supplement the existing data in the literature to counsel new patients in terms of realistic expectations of success following PGT‐M and PGT‐SR. Abstract : What is already known about this topic? To our knowledge, three studies have been published on PGT‐M and PGT‐SR embryo outcomes. One was in London, one was in France, and one in China. What does this study add? To our knowledge, this is the only review of PGT‐M and PGT‐SR embryo and pregnancy outcomes published in North America. This paper explains how the information can help improve genetic counseling patients considering PGT‐M and PGT‐SR.